Tumpang Tindih Kewenangan Penyidikan Badan Narkotika Nasional dengan Kewenangan Penyidikan Kepolisian Republik Indonesia - Sahid, M. (Penerbit STKIP PGRI Bangkalan, 2018)
Abstract Authority to conduct criminal investigations of narcotic regulated under Law No. 35 of 2009 on Narcotics, namely article 81 of the law. Dibeikan investigative authority to the national drug agencies and the police of the republic of Indonesia. With the division of the investigative authority of overlap and multiple interpretations of article 81 of Law No 35 of 2009 on Narcotics. This paper aims to analyze the rules of authority narcotics investigation of criminal offenses. This paper is based on research using the normative approach to law (statute approach) and the conceptual approach (conceptual approach). The results showed that the regulation of narcotic crime investigation authority should be clarified and given limit, so in practice the rule of law is not a clash of authority between the National Narcotics Agency to police the Republic of Indonesia. As well as law enforcement agencies in carrying out their duties effectively and goes in accordance with the criminal justice system. Key words :Authority Investigation, Crime, Narcotics